The Effectiveness of Group Counseling with Constructive Criticism Techniques to Reduce Students' Social Bullying Behavior in Man 1 Deli Serdang - Putri Aulia Prayoga; Purbatua Manurung (MASI Mandiri Edukasi, 2025)
This study addresses the growing concern of social bullying among students, particularly behaviours such as exclusion, rumour-spreading, and ridicule that negatively affect students’ psychological and social development. The objective of this research is to analyze the effectiveness of group counseling, utilizing the constructive criticism technique, as an intervention to reduce social bullying behavior among students at MAN 1 Deli Serdang. This study applied a quasi-experimental research method with a pretest-posttest control group design. A total sample of 65 students was selected through purposive sampling and assigned to experimental and control groups. Data were collected using observation and a Likert-scale questionnaire to assess changes in students’ social bullying behaviour before and after the counselling intervention. Data analysis was performed using paired-sample t-tests to measure the significance of behavioural improvement. The research findings indicate a significant decrease in social bullying behaviour among students who participated in group counselling using the constructive criticism technique (p = 0.001). This technique effectively enabled students to receive constructive feedback, enhance self-awareness, and foster positive social interactions. In conclusion, the constructive criticism technique in group counselling has been proven to be an effective intervention in reducing social bullying behaviour among students, thereby contributing to a safer and more supportive school environment.